Wybrane zagadnienia informatyzacji sądowego postępowania egzekucyjnego : elektroniczna komunikacja sądowych organów egzekucyjnych z administracyjnymi organami egzekucyjnymi i podatkowymi oraz bankami - Janus, Monika (Wydawnictwo C.H. Beck, 2022)
The aim of this article is to justify the purpose and usefulness of creating in 2016, at the second stage of computerization, enforcement proceedings (the electronic application system between bailiffs and administrative enforcement authorities, tax authorities and e-communication with banks in the context of meeting the objectives) in order to increase the effectiveness and speed of enforcement proceedings and optimization of work processes in a bailiff’s office.
Keywords: informatization of enforcement proceedings; electronic application system; teleinformation system; e-attachment of bank account; electronic actions